GIS-based Analysis of the Impact of Mass Rapid Transit on Accessibility and Spatial Equity in Jakarta - Wibowo, Sony Sulaksono; Silaen, Liora Parulian Bitya Joanna; Sjafruddin, Ade; Weningtyas, Widyarini (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2025)
Mass rapid transit (MRT), inaugurated in 2019 by the DKI Jakarta Provincial Government, was designed to address the city's transportation challenges by improving accessibility and reducing spatial disparities. This study assessed the MRT’s impact on accessibility and spatial equity, specifically regarding travel time, economic potential, and travel fares. Primary data was collected through a questionnaire to identify passengers' origins and destinations, which was used to analyze the catchment area and calculate real-time travel times during peak hours via a navigation application. Secondary data helped calculate accessibility and spatial equity for two scenarios: with and without the MRT. GIS (Geographic Information System) was used to facilitate a visual understanding of the findings. The analysis revealed that while the MRT improved overall accessibility regarding travel time and economic potential, it failed to reduce travel fares, which are higher than those of other public transportation options like Jaklingko, TransJakarta, and KRL. Moreover, the MRT operation worsened spatial disparities, increasing the gap in accessibility between different areas of the city. In conclusion, while MRT has succeeded in enhancing travel efficiency and boosting the economic potential of several regions, it has also highlighted a growing spatial inequality, particularly regarding travel fares, which remain a challenge for equitable access to transportation across Jakarta.